2020
DOI: 10.1002/jum.15559
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Assessment Method With Ultrasound for Obstructive Tonsillar Hypertrophy in Children

Abstract: Objectives-To develop a new method for the objective evaluation of airway obstruction due to tonsillar hypertrophy using ultrasound (US) in children.Methods-The oropharynx was examined in patients, and tonsil grades were evaluated according to the staging system of Brodsky et al (Int J Pediatr Otorhinolaryngol 1987; 13:149-156). The narrowest intertonsillar distance (ITD) and widest transverse length of the tongue base (TLTB) were then measured by US, and their ratio was calculated. The clinical value of US w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The current study involved adult participants and showed insignificant relationship of tonsillar grading with age, as tonsillar size increases in childhood and stabilizes thereafter. Effect of BMI which was considered in their study showed no impact on tonsil volume in children and adults which concurs with the present study findings 15 .…”
Section: Discussionsupporting
confidence: 92%
“…The current study involved adult participants and showed insignificant relationship of tonsillar grading with age, as tonsillar size increases in childhood and stabilizes thereafter. Effect of BMI which was considered in their study showed no impact on tonsil volume in children and adults which concurs with the present study findings 15 .…”
Section: Discussionsupporting
confidence: 92%